An overview of metamaterials and their achievements in wireless power transfer. Issue 12 (7th March 2018) - Sun, Kai; Fan, Runhua; Zhang, Xihua; Zhang, Zidong; Shi, Zhicheng; Wang, Ning; Xie, Peitao; Wang, Zhongyang; Fan, Guohua; Liu, Hu; Liu, Chuntai; Li, Tingxi; et al.
Abstract : The schematic of metamaterials applied in wireless power transfer. Abstract : Metamaterials have been deployed for a wide range of fields including invisible cloak, superlens, electromagnetic wave absorption and magnetic resonance imaging, owing to their peculiar electromagnetic properties. However, few investigations on metamaterials were focused on wireless power transfer (WPT). WPT is the transmission of electrical energy from a power source to an electrical load without conductors like wires or cables. Metamaterials can enhance the transfer efficiency and enlarge the transfer distance due to their ability of focusing magnetic flux, which opens up a novel approach to promoting the development and application of WPT. This review paper aims to provide an overview of the fabrications, exotic properties, and their applications especially in the WPT field. Meanwhile, the perspective and future challenges of metamaterials and WPT are proposed.